A comparative study on knowledge, attitude, and practice of injection safety among nurses in two hospitals in Ibadan, Nigeria - Adejumo, Prisca Olabisi; Dada, F A (International Journal of Infection Control, 2013)
ABSTRACT Medical treatment is intended to save life and improve health, and health workers have a responsibility to prevent transmission of health-care associated infections. Adherence to safe injection practices and related infection control is part of that responsibility.1 This comparative study was carried out in two hospitals in Nigeria. Participants were selected conveniently while data were collected with the aid of questionnaire. A sum of 385 nurses took part in the study following ethical approval. The mean age of the respondents was 37 years and 92.5% were females. All have heard about injection safety. Their knowledge level was high, 70.4% associated unsafe injection with blood-borne infection, 55.9% had correct information that two handed recapping is not a safe injection practice, 84.4% claimed that contaminated sharps predisposes the community to bio-hazards, and 293 (76.1%) had correct information that used syringes and needles should be discarded in a sharp waste box. However, the high knowledge was not translated to practice. About half of them (50.4%) of the participants recently sustained sharp injury through intramuscular and subcutaneous injections. Only 15.6% of this number reported the injuries to their institution. Out of the total respondents, 62.9% did not know that their hospitals have injection policies, while 53.2% said that nurses are not involved in such policies. Doctors were alleged by 79.5% as health care workers who most frequently leave sharps at the patients’ bed side. Therefore, nurses as the nerve center of the healthcare enterprise must be advocate of safe injection practices. Key words: Adeoyo Maternity Hospital, Injection safety, Nurses, Practices, UCH